The Cognitive Shortcuts for Social Influence of MSME Food and Beverage Ads: The Corpus Based Analysis - Edel, Eky Erlanda; Kurniawan, Eri; Supriadi, Rinaldi (e-Journal of Linguistics; Vol 20 No 1 (2026): ejl-January, 2025)
This study conducts a corpus-based analysis of MSME catalogs to illustrate how the cognitive shortcuts of persuasion techniques can effectively influence the target customer in food and beverage promotion, particularly from a psychological perspective. This qualitative descriptive study investigates a specialized corpus of MSME food and beverage promotions derived from the product catalogs at BRI EXPO (RT) 2025 from 6 categories of the cognitive shortcuts: authority, social proof, consistency, reciprocity, scarcity, and linking to increase social influence by Cialdini’s Principles of Persuasion. The data consists of product descriptions within the food and beverage category, resulting in 6814 tokens. The data is categorized using concordance software Sketch Engine. The data analysis used domain, taxonomic, componential, and cultural theme analysis. The final findings of this research reveal that MSME food and beverage ads predominantly use the cognitive shortcuts of commitment, reciprocity, scarcity, and social proof to persuade consumers linguistically. These shortcuts are often represented through verbs and adjectives emphasizing quality, trust, exclusivity, and community validation. Each product category applies these shortcuts differently, reflecting both market positioning and cultural values. While authority and liking are less frequently used, their inclusion could enhance emotional and credibility-based appeal. It is clear that this study contributes to the marketing corpus, particularly on promotion catalogs of MSMEs.